DOES DIGITAL MARKETING BASED ON BRAND IMAGE AND BRAND TRUST AFFECT PURCHASE DECISIONS IN THE FASHION INDUSTRY 4.0? - Ilmi, Sayyidah Hafidhatul; Harianto, Eric; Azizurrohman, Muhammad; Mas’ud, Riduan (Jurnal Aplikasi Manajemen, 2023)
Factors forming purchasing decisions are important for companies to analyze to be sustainable in rapid technological developments. The rapid development of technology is followed by e-commerce in Indonesia, which results in increasingly fierce competition between competitors. This study aims to analyze and examine the impact of digital marketing on brand trust and brand image that influence the purchase decision of Mirrorplus.id products. Data collection uses quantitative methods by distributing questionnaire to Mirrorplus.id consumers. The study was conducted from July 2021 to January 2022. The sampling technique used purposive sampling with several criteria and 139 respondents. The data analysis technique used SEM-PLS with the help of SmartPLS 3.2.9. The results of the study yield several conclusions, namely, digital marketing has a significant and positive effect on brand image and brand trust, brand image does not have a significant but positive effect on purchasing decisions, and brand trust has a significant and positive effect on purchasing decisions. The implication that will be carried out is to carry out a market penetration and product development strategy. Market penetration can be done by adding promotion and marketing costs to MirrorÂplus.id digital media. Some steps can be taken are collaborating with several influencers, where influencers can spread the Mirrorplus.id brand by explainÂing product functions and values.